ANALISIS SEKTOR UNGGULAN KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - B21109007, Iman Santoso (Jurnal Pembangunan dan Pemerataan, 2016)
The research aims to do "LEADING SECTOR OF ANALYSIS IN KUBU RAYA REGENCY WEST KALIMANTAN" which is basically to identify and analyze the leading sector, how to change and shift, how classification and its interaction with other regencies / cities bordering directly with Kubu Raya. The methodology used in this research is descriptive method, based on secondary data from BPS BPS West Kalimantan and Kubu Raya. The analytical tool used include analysis Location Quotient (LQ), Shift Share Analysis, Typology Klassen Sectoral and Gravity Model Analysis. Location Quotient analysis results show that in 2014, main sectors in Kubu Raya is the Sector Procurement of Electricity and Gas, Manufacturing Sector, and Sector Transportation and Warehousing. According to the Shift Share Analysis, the composition of the sector in Kubu Raya moving more slowly than the average composition of the sector in the GDP of West Kalimantan Province. Results Sectoral Analysis Model Typology Klassen shows that the Electricity and Gas Supply Sector, Manufacturing Sector, and Sector Transportation and Warehousing included in the category of advanced economic sectors and can grow quickly. According to the Gravity Model Analysis, the greatest strength of the interactions that occur between Kubu Raya to Pontianak. Keywords: Leading Sector, Analysis of Location Quotient (LQ), Shift Share Analysis, Typology Klassen Sectoral, Analysis of Gravity Model.